Risk Analysis of Vapour Cloud Explosions for Oil and Gas Facilities - Ma, G.; Huang, Y.; Li, Jingde (Springer, 2019)
This book focuses on describing and applying risk analysis of vapour cloud explosions (VCEs) in various oil and gas facilities, such as petrol stations, processing plants, and offshore platforms.